Are Welsh primary schools Sunproofed? Results of a national survey Part 2: sun protection practices in primary schools in Wales - Daniel Tod (Clinical and Experimental Dermatology, 2024)
Background: Skin cancer rates are on the rise globally. School sun safety programmes are recommended by the World Health Organisation to reduce the risk of future skin cancer at population level; however, these are encouraged but not mandated in Wales. Objectives: To explore current sun protection practices and sun safety education in primary schools in Wales and whether these are linked to the existence of a formal sun safety policy. Methods: An online survey to all 1241 Welsh primary schools asking about sun safety practices, education and formal policies. Results: 471 (38.0%) schools responded with the profile of responding schools generally matching the profile of schools in Wales. A minority (22,4.7%) of responding schools reported they had sufficient shade for most activities. In the spring and summer terms almost two thirds of schools encourage hat wearing (304, 64.8%) and sunscreen (296, 63.2%). While nearly all schools reported that parents were encouraged to apply sunscreen to students before school (449, 95.7%), there was wide variation in other sunscreen application practices. Less than one third of schools (129, 29.0%) reported that they include sun protection education in the curriculum in every year group, with 11.7% (52) including this in certain years only. Schools with a formal policy were more likely to report more comprehensive sun protection practices including having sufficient shade [OR 1.51, 95% CI 1.04-2.19; p = 0.032], having spare hats for pupils to wear [OR 1.59, 95% CI 1.07-2.37; p = 0.023], providing guidance for staff [OR 5.87, 95% CI 3.05-11.28; p < 0.001], encouraging them to model sun safe behaviours [OR 1.82, 95% CI 1.18-2.80; p = 0.007] and teaching sun protection education as part of the curriculum in every year group [OR 2.56, 95% CI 1.76-3.71; p < 0.001]. With respect to sunscreen, the existence of a formal policy did not seem to affect a school’s practice. Conclusions: While in most cases, the existence of a formal policy suggests more comprehensive sun protection practices and education in schools, sun protection measures and education need improvement across the primary school sector in Wales to reverse rising skin cancer rates.